BBNJ Agreement and the Negotiation Process: an Analysis From Developing Country Perspective With Special Focus on Indonesia - K K, Simi; Chalakkal, Kavitha (UI Scholars Hub, 2025)
The governance of marine genetic resources from areas beyond national jurisdiction (ABNJ)and regulating access to this regime in all available and existing forms is a core issue before international policymakers. The recently concluded BBNJ Agreement negotiations for the conservation and sustainable use of marine biological resources from areas beyond national jurisdiction was a platform to negotiate for a new legal instrument to address the core issues related to marine diversity from ABNJ, as agreed under the UNGA Resolution 72/249 to address the problems identified in the 2011 package. Defining MGRs and developing appropriate access and benefit-sharing mechanisms for marine biological resources was a matter of concern for developing and underdeveloped countries. The conflicting interests of technically advanced nations on one side and the developing, least developed, and underdeveloped countries on the other hand were highly debated during the negotiation process. The outcome of Part I and II that regulate access and benefit sharing under the BBNJ Agreement will have a broader impact on the interests of developing states and raise implementation challenges of the instrument that will be revealed to the fullest extent only once the Agreement enters into force. The paper will make a critical analysis of the BBNJ negotiation process and its outcome, on access and benefit sharing, focusing on Part I and II of the Agreement, from the Intergovernmental Conferences (IGC) and the submissions by developing/ states, with a particular focus on Indonesia and India, to understand the outcomes, and the extend of the reflection of the interests of states in the final text.